The correct answers are:
13 + 3 ÷ 3 = 1(13 + 3 ÷ 3)
13 + 3 ÷ 3 = 13 + 1
13 + 3 ÷ 3 = 13 + 3 ÷ 3 + 0
Let's look into them one by one:
13 + 3 ÷ 3 = 1(13 + 3 ÷ 3)
As anything multiplied by one will not have changes in value, this is correct.
13 + 3 ÷ 3 = 13+(3÷3) = 13 + 1
As 3÷3 is 1,this is also correct.
13 + 3 ÷ 3 = 13 + 3 ÷ 3 + 0
As anything plus zero will not have a chnage in value, this is correct.
The incorrect option:
13 + 3 ÷ 3 ≠ 16 ÷ 3
Unless there are brackets indicating addition has to be done first, devision comes before addition hence this is not correct.
Hope it helps!